Glutathione Deficiency in Sinorhizobium meliloti Does Not Impair Bacteroid Differentiation But Induces Early Senescence in the Interaction With Medicago truncatula - Yang, Li; El Msehli, Sarra; Benyamina, Sofiane; Lambert, Annie; Hopkins, Julie; Cazareth, Julie; Pierre, Olivier; Hérouart, Didier; Achi-Smiti, Samira; Boncompagni, Eric; Frendo, Pierre (Frontiers in Plant Science, 2020)
Legumes are able to interact symbiotically with Rhizobia. This interaction gives rise to a new organ, named nodule. Nodules are characterized by an increased glutathione (GSH) content compared to roots. In order to characterize the modification of nodule activity induced by the microsymbiont glutathione deficiency, physiological, biochemical and gene expression modifications were analysed in nodules after the inoculation of Medicago truncatula with the SmgshB mutant of Sinorhizobium meliloti which is deficient in GSH production. The decline in nitrogen fixation efficiency was correlated to the reduction in plant shoot biomass. Flow cytometry analysis showed that S. meliloti SmgshB bacteroids present a higher DNA content than free living bacteria. Live/dead microscopic analysis showed an early bacteroid degradation in SmgshB nodules compared to control nodules. Finally, the expression of two marker genes involved in nitrogen fixation metabolism, leghemoglobin and nodule ncr001, decreased significantly in mutant nodules at 20 dpi. In contrast, the expression of two marker genes involved in the nodule senescence, cp6 and purple acid protease, increased significantly in mutant nodules at 10 dpi showing that an early senescence process occurs in SmgshB nodules. Our results showed that bacterial GSH deficiency does not impair bacterial differentiation but induces an early nodule senescence.